Konsep Keselamatan Menurut Rasul Paulus: Kajian Historis Kritis Dalam Roma 5:1-2 dan Implikasinya Bagi Orang Kristen - Delon Patrick F Musa; Marthinus Ngabalin (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
This writing focuses on three main objectives, namely: To explain the concept of safety in general; Describe the concept of salvation according to Paul in Romans 5;1-2; Describe the implications for Christians today regarding salvation. The Method used is a qualitative method with a literature study approach. Meanwhile, the interpretation approach used is the critical historical method. The result of this writing is that the concept of salvation according to Paul in Romans 5: 1-2 emphasizes three aspects, namely: salvation in the past, present and future. Christians realize that salvation is central to their lives. And the center of that salvation is in Jesus Christ.